The Influence of Artificial Intelligence and Emerging Technologies on Diagnostic Precision and Treatment Strategy in General Medicine, Dentistry, and Anesthesia: A Comprehensive Review - Qubty, Meshari Abdullah Ali; Al Shamer , Abdullah Ahmed Jobran; Al Damjan, Sattam Bin Shaya Ali; Alsharari, Ahmed Matar Dubayyan; Alkibari, Sultan Sauoed A; Salamah, Abdulraouf; Refaei, Khalid Mahdi Bin Mohammed; Almutayri, Abdulmajeed Matar Matir; Sultan, Amnah Abdu; Eidah, Waheed Qassem; Qubty, Meshari Abdullah Ali; Alaradi, Reem Sulaiman Atallah; et al. (Journal of Ecohumanism, 2024)
From general medicine to dentistry to anesthesia, the integration of artificial intelligence (AI) and sophisticated technology in healthcare has transformed diagnosis and treatment planning across many disciplines. The many ways in which artificial intelligence (AI), virtual reality (VR), augmented reality (AR), and other new technologies could improve patient care and clinical results are investigated in this work.With an eye on the use of artificial intelligence and immersive technologies in surgery planning, patient care, and diagnostic imaging, a thorough study of the present literature was undertaken. Analyzed were many studies to evaluate in clinical environments the efficiency, accuracy, and possible advantages of these technologies.The results suggest that AI substantially enhances diagnostic accuracy and efficiency, particularly in the interpretation of dental radiographs and the determination of treatment strategies. Technologies such as VR and AR have shown the potential to lower patient anxiety during treatments and improve dental practitioners' teaching opportunities. Particularly, AI systems showed an amazing success rate in identifying diseases like periodontitis, and VR treatments helped young patients to be less uncomfortable.The results emphasize the transformative potential of AI and immersive technologies in the healthcare sector. These developments will help to raise the general quality of treatment given in general medicine, dentistry, and anesthesia by enhancing clinical decision-making and improving patient experiences. To fully appreciate their advantages and solve issues like implementation expenses and the necessity of training, constant research and development are needed.